2021
DOI: 10.3390/jmse9111281
|View full text |Cite
|
Sign up to set email alerts
|

A Stereo Matching Method for 3D Image Measurement of Long-Distance Sea Surface

Abstract: Tsunamis are some of the most destructive natural disasters. Some proposed tsunami measurement and arrival prediction systems use a limited number of instruments, then judge the occurrence of the tsunami, forecast its arrival time, location and scale. Since there are a limited number of measurement instruments, there is a possibility that large prediction errors will occur. In order to solve this problem, a long-distance tsunami measurement system based on the binocular stereo vision principle is proposed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We solve this problem by adding a disparity initialization, which can produce the approximate location of the target sea wave in the right image based on the location of the detected sea wave in the left image. Disparity initialization is conducted within the sea surface image based on our previous work [55], assuming the pixel coordinate in the vertical direction is y. From the top of the image to the bottom, y increases, and we found that disparity d increases when y increases; in other words, the relationship between y and d is approximately proportional, as Figure 7 shows.…”
Section: Disparity Initialization and Matchingmentioning
confidence: 80%
See 1 more Smart Citation
“…We solve this problem by adding a disparity initialization, which can produce the approximate location of the target sea wave in the right image based on the location of the detected sea wave in the left image. Disparity initialization is conducted within the sea surface image based on our previous work [55], assuming the pixel coordinate in the vertical direction is y. From the top of the image to the bottom, y increases, and we found that disparity d increases when y increases; in other words, the relationship between y and d is approximately proportional, as Figure 7 shows.…”
Section: Disparity Initialization and Matchingmentioning
confidence: 80%
“…A Siamese CNN backbone is used to extract feature maps from template z and search image x. Template z is a cropped section of size h × w centered on the object obtained by a detection module. The search image x is a larger image centered on the estimated position of the object in another image; in this paper, it was obtained in our previous work [55]. To compare the difference between the template and search image, a depth-wise cross-correlation represented by ⋆d is selected to produce a multi-channel response.…”
Section: Sea Wave Matching Modulementioning
confidence: 99%
“…For example, Jiang Wenzheng built a mathematical model of wave characteristics based on the least square method and the wave surface theory, and proposed a measurement method of wave height without sea surface control points. Yang [1] Proposed a matching descriptor based on the physical characteristics of sea waves to solve the matching difficulties caused by the texture similarity of sea surface images, and established the relationship between parallax and y coordinate to reduce the matching search range. Lu [2] and others applied binocular stereo photography to bed shape measurement, providing high-precision data and effective technical methods for studying the macro motion characteristics of bed shape under different boundary conditions.…”
Section: Introductionmentioning
confidence: 99%